Soil sensing: A new paradigm for agriculture. (October 2016) - Viscarra Rossel, Raphael A.; Bouma, Johan
Abstract: Last century, during the 'Green Revolution' the use of synthetic fertilizers contributed to increased agricultural production. However, their use did not reflect local soil and water conditions because recommendations were developed for larger agro-ecological zones. They only focused on increased productivity, neglecting any adverse environmental consequences. Largely, this legacy remains and recommendations are still made using 'top-down' procedures based on limited data and generic, empirical relations between soil nutrient contents, fertilization rates and yields. Using soil sensors in agriculture can fundamentally change this approach by allowing innovative 'bottom-up' approaches that characterize local soil and environmental conditions in space and time, improving the efficiency of production to maximize farm incomes and minimize environmental side effects. The sensed information can be used to build site-specific databases of relations between soil and plant condition and growth. Recent technological developments in sensing coupled with ongoing advances in information and communication technologies have given ground to a renewed interest in soil sensing and its use in different applications at different spatial scales. Soil sensing can facilitate the measurement and monitoring of the soil's physical and biochemical attributes (e.g. nutrients, water) to better understand their dynamics, their interactions with the environment while considering their large spatial heterogeneity. The new sensing methods can also be used to effectively monitor soil organic carbon and be central to the adoption of best agronomic practices that also allow carbon sequestration and a reduction of greenhouse gas (GHG) emissions. Thus, sensing can help us to better articulate the potential of soil to meet the world's needs for food, fiber, climate adaptation and environmental sustainability allowing the design and implementation of innovative management practices and policy aimed at sustainable development. Highlights: Due to technological developments and advances in ICT soil sensing is operational. Soil sensing enables the development of innovative approaches to help improve the efficiency of agricultural production. Soil sensing is central to the adoption of best agronomic practices, carbon sequestration and reduction of GHG emissions. Soil sensing can support new science and policy to help meet our need for food, climate adaptation and environmental quality.